Visceral Adipose Tissue Is Associated With Stricturing Crohn's Disease Behavior, Fecal Calprotectin, and Quality of Life. Issue 3 (12th September 2018) - Bryant, Robert Venning; Schultz, Christopher G; Ooi, Soong; Goess, Charlotte; Costello, Samuel Paul; Vincent, Andrew D; Schoeman, Scott; Lim, Amanda; Bartholomeusz, Francis Dylan; Travis, Simon P L; Andrews, Jane Mary
Abstract: Background: Visceral adipose tissue (VAT) has been proposed to play a pathogenic role in Crohn's disease (CD); however, prospective clinical data are lacking. The aim was to evaluate whether VAT, beyond body mass index (BMI), is associated with CD behavior, disease activity, quality of life (QoL), or outcomes. Methods: Body composition data and clinical, anthropometric, disease activity (fecal calprotectin [FC]), and QoL scores were gathered prospectively on adults with CD at 0, 12, and 24 months. BMI and, VAT metrics (visceral adipose tissue volume [cm 3 ]/height [m 2 ] index and VAT:subcutaneous adipose tissue [SAT] ratio) were calculated. Inflammatory bowel disease–related surgery and hospitalization were recorded over extended follow-up (median, 51 months). Multivariable linear mixed effects and logistic regression analyses were performed. Results: Ninety-seven participants were assessed at baseline (55% male; median age, 31 years), 84 at 12 months, and 72 at 24 months. VAT:SAT was positively associated with stricturing disease behavior (log odds ratio [OR], 1.7; 95% confidence interval [CI], 0.32 to 3; P = 0.01) and elevated FC in patients with ileocolonic disease (β, 1.3; 95% CI, 0.32 to 2.3; P = 0.01). VAT:SAT was associated with lower QoL, particularly in those with ileal disease (β, –12; 95% CI, –19 to –4.5; P = 0.05). However, no prospective associations were observed between serial VAT measurements and time to surgery or hospitalization. No correlations were found between BMI and disease behavior, activity, or QoL. Conclusions: VAT:SAT, rather than BMI, is associated with stricturing CD behavior, elevated FC, and reduced QoL in a disease distribution–dependent manner. Further studies are required to substantiate the role of VAT as a useful biomarker in CD.